Neischnocolus iquitos, una especie nueva de Perú (Araneae: Theraphosidae: Theraphosinae) - Kaderka, Radan (2020)
Neischnocolus iquitos sp. nov. from Loreto region, Peru, is described, diagnosed and figured. Males of N. iquitos sp. nov. differ from all known congeners in the presence of two retrolateral processes on palpal tibia, in combination with the presence of a retrolateral keel on embolus and the absence of granulation or microspikes on embolus or tegulum. Females of N. iquitos sp. nov. differ from all known Neischnocolus females in the morphology of the genitalia consisting of a lower sclerotized part with two short, separate seminal receptacles, and an upper part, which is transparent and notched. ________________________________________________________________Publicación registrada en Zoobank/ZooBank article registered:LSIDurn:lsid:zoobank.org:pub:4854FB77-99B5-4208-9394-DBA7BB5EC64FActo nomenclatural/nomenclatural act:Neischnocolus iquitos Kaderka, 2020LSIDurn:lsid:zoobank.org:act:F5FB8A3E-922A-47AC-B5B2-B575C206B39D________________________________________________________________